Selecting Sampling Interval in the Improved Spectral Domain Method to Simulate Microstrip Circuits - Gong, Zhuqian; Mittra, Raj; Yu, Wenhua; Yang, Xiaoling; Guo, Jianyan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, we investigate the spectral method that calculates the S-parameters for microstrip circuits and antennas. A sampling interval selection criterion is proposed. The scheme for low-loss cases is specially discussed. Several examples are employed to demonstrate the engineering applications of the spectral domain method and its results are compared with previously published and measured results.